2019
DOI: 10.1021/acsaem.9b00795
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Nanocrystal Aerogels as Electrolyte Scaffolds for Glass and Plastic Dye-Sensitized Solar Cells

Abstract: The fabrication, thickness, and structure of aerogel films composed of covalently cross-linked cellulose nanocrystals (CNCs) and poly(oligoethylene glycol methacrylate) (POEGMA) were optimized for use as electrolyte absorbers in dye-sensitized solar cells (DSSCs). The aerogel films were cast directly on transparent conducting counter electrode substrates (glass and flexible poly(ethylene terephthalate) plastic) and then used to absorb drop-cast liquid electrolyte, thus providing an alternative method of fillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…[132] The DSSC has the advantages compared to ordinary solar cells in its low cost by using inexpensive materials and the easy way of fabrication due to the variety of suitable materials and preparation methods, for example, by using roll-to-roll processes. [133][134][135][136] Usually the electrolyte is in a liquid form, which is pumped through the cell. There, the liquid is exposed to a porous structure modified with a dye/TiO 2 layer.…”
Section: Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…[132] The DSSC has the advantages compared to ordinary solar cells in its low cost by using inexpensive materials and the easy way of fabrication due to the variety of suitable materials and preparation methods, for example, by using roll-to-roll processes. [133][134][135][136] Usually the electrolyte is in a liquid form, which is pumped through the cell. There, the liquid is exposed to a porous structure modified with a dye/TiO 2 layer.…”
Section: Solar Cellsmentioning
confidence: 99%
“…This system showed similar performance and stability as the nonaerogel DSSCs and enables the production of large-area solar cell systems. [134] The beneficial effect of nanoscale microfibrillated cellulose (MFC) was investigated by Chiappone et al For this purpose, nanoscale microfibrillated cellulose was used in photocrosslinked polymer electrolyte membranes. Here, the MFC serves as a source for light scattering and reflection.…”
Section: Solar Cellsmentioning
confidence: 99%
“…Few studies have been successfully reported demonstrating the enhanced performance of dye-sensitized solar cells with xerogel-structured photoanodes. [44][45][46][47] These results encouraged the present approach to synthesize the vanadium nitride xerogel and investigate its catalytic activity towards the counter electrode for DSSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a quasi‐solid electrolyte system provides a pathway for the solution of both the above‐mentioned problems, and the hierarchical cross‐link structures of the natural cellulose substances make them the ideal scaffold for the liquid electrolyte to form the quasi‐solid electrolyte system. As an example, a cotton derived cellulose aerogel film was covalently anchored with poly(oligoethylene glycol methacrylate (POEGMA), and then cast on the counter electrode substrate as the electrolyte absorber in the DSSC [87b] . The yielded cellulose aerogel film (CNC‐POEGMA aerogel film) exhibited a three‐dimensionally cross‐link network structure with high porosity that replicated from the initial cellulose substance.…”
Section: Natural Cellulose Substances Based Materials For Solar Cellsmentioning
confidence: 99%